Rol de la participación comunitaria en el abordaje de condiciones nutricionales asociadas a vulnerabilidad: Experiencia en Liga de los Barrios, Santa Fe La Capital (SigMe, 2023)
The participation of the community has a fundamental role in the identification of socio-health issues in different contexts. The current article analyzes the information brought from the Liga Infantil de los Barrios which is a group of people that gathers different families of popular neighbourhoods for recreational purposes and where anthropometric measures are carried out with the aim of detecting vulnerable situations. The findings visualize the risk of overweight or obesity in children as well as chronic malnutrition in this group of people. Meanwhile, there is an increasing percentage of body mass in adult women who assist this group.
Keywords: Community participation; Malnutrition; Vulnerability